Perform the indicated operation.
(2x - 4y)(2x + 4y)

Question

Asked 3/16/2016 10:16:58 AM

Updated 3/16/2016 11:52:16 PM

4 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by arel [3/16/2016 6:43:19 PM]

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

2(2) - 4(4)

= 4 - 16

= -12

Question

Asked 3/16/2016 10:16:58 AM

Updated 3/16/2016 11:52:16 PM

4 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by arel [3/16/2016 6:43:19 PM]

Rating

8

(2x - 4y)(2x + 4y)

= 2x*2x - 4y*2x + 2x*4y - 4y*4y

= 4x^2 - 8xy + 8xy - 16y^2

= 4x^2 - 16y^2

= 2x*2x - 4y*2x + 2x*4y - 4y*4y

= 4x^2 - 8xy + 8xy - 16y^2

= 4x^2 - 16y^2

Added 3/16/2016 6:43:13 PM

This answer has been confirmed as correct and helpful.

8

Write the nth term of the following sequence in terms of the first term of the sequence 1, 8, 15, 22, . . . is 7n - 6.

The common difference = 22 - 15 = 7;

nth term = 1 + (n - 1)*7 = 7n - 7 + 1 = 7n - 6

The common difference = 22 - 15 = 7;

nth term = 1 + (n - 1)*7 = 7n - 7 + 1 = 7n - 6

Added 3/16/2016 6:44:53 PM

This answer has been confirmed as correct and helpful.

8

x^2(2x^3 - 3) - 3x(x + 4)

= 2x^5 - 3x^2 - 3x^2 - 12x

= 2x^5 - 6x^2 - 12x

= 2x^5 - 3x^2 - 3x^2 - 12x

= 2x^5 - 6x^2 - 12x

Added 3/16/2016 11:52:16 PM

This answer has been confirmed as correct and helpful.

5

x^2(2x^3 - 3) - 3x(x + 4)

= x^2*2x^3 - x^2*3 - 3x*x - 3x*4

= 2x^5 - 3x^2 - 3x^2 - 12x

= 2x^5 - 12x

= x^2*2x^3 - x^2*3 - 3x*x - 3x*4

= 2x^5 - 3x^2 - 3x^2 - 12x

= 2x^5 - 12x

Added 3/16/2016 6:43:57 PM

This answer has been flagged as incorrect.

Flagged by Andrew. [3/16/2016 11:52:21 PM]

3ay(a + 2y)2 =

Question

Updated 3/16/2016 9:48:08 AM

1 Answer/Comment

3ay(a + 2y)^2 = 3a^3y + 12a^2y^2 + 12ay^3

Added 3/16/2016 9:48:08 AM

This answer has been confirmed as correct and helpful.

Factor the following polynomial completely.
20x2 + 22xy + 6y2 =

Question

Not Answered

Updated 3/16/2016 10:25:21 AM

1 Answer/Comment

Work the item as directed.
Factor 24x2 - 6xy -63y2 completely.

Question

Not Answered

Updated 3/16/2016 8:58:05 PM

1 Answer/Comment

Factor completely the following quadratic expression.
9x2 + 24xy + 16y2

Question

Updated 3/16/2016 8:59:43 PM

1 Answer/Comment

39,058,804

questions answered

There are no comments.